An Analysis of Performance in Free-Space Optical Communication Using Eight Wavelength Division Multiplexing (Texas Journal of Engineering and Technology, 2023)
This article's main goal is to carry out an in-depth analysis of the free space optic channel's performance. The ultimate goal is to address the various obstacles associated with terrestrial infrastructure and channel leasing. In this article the four channels provided by the wavelength-division multiplexing (WDM) transmitter and transmitted to the Free-space optical communication (FSO) transceiver, resulting in successful reception of output signals at a speed of 10 Gbps, with a free channel range of 200m. The best iteration achieved an attenuation of 25dB/km. The optisystems software simulation package conducted 10 iterations, and the average total power was measured to be -34.22 dBm, while the maximum average Q-factor was 114.43. These results are considered satisfactory for the entire project, as they indicate low data error rates. (9 pt) .